Sosio-Politik Orang Bugis dan Islamisasi Masyarakat Sulawesi Timur di Zaman Kolonialisasi Belanda - Muhammad Dalle; Muhammad Jundi (HEURISTIK: Jurnal Pendidikan Sejarah, 2021)
In the era of Dutch colonialism in Indonesia, with the trilogy of Western imperialism Gold, Gospel, and Glory, they not only came to dominate Indonesia's wealth but also extracted and embodied the faith of Muslims. In Central Sulawesi, many Christian missionaries were sent by the Dutch to sow the teachings of the Gospel so that to this day there are Christian congregation centers there. Areas with a strong Christianity are Poso and its surrounding areas in the interior, but at the same time, many inland and coastal areas in eastern Sulawesi are also very Muslim. One of the emerging identities in the community and network of the Bugis people. This study aims to determine the socio-political dynamics of the Bugis people and the Islamization of society in the East Sulawesi region. The approach used is a qualitative approach, with the type of literature study research, and Miles and Huberman's data analysis models, namely: data reduction, data display, and a conclusion or drawing or verifying. Based on the research results, the Bugis people are one and even the only ethnic group that has influenced East Sulawesi the most in terms of Islamic belief, which is predominantly dominated by the Bone Bugis. And the interaction patterns they built in the process of Islamization of the people of East Sulawesi, there are 5, namely: 1) Syiar Da'wah, 2) Trade (economy), 3) Settlement (Marriage), 4) Politics, 5) Education.